An Exoskeleton Design and Numerical Characterization for Children with Duchenne Muscular Dystrophy - Cristian Copilusi; Sorin Dumitru; Nicolae Dumitru; Ionuț Geonea; Cristian Mic (Bioengineering)
This research addresses a feasibility study for validating an exoskeleton with kinematic considerations. The designed exoskeleton will be used for children with congenital disorders, especially for a case study characterized by Duchenne muscular dystrophy (DMD). The research core focuses on virtual simulations carried out through the multibody systems theory under an MSC Adams 2012 software environment, with an exoskeleton constructive solution. The designed exoskeleton mechanism is characterized by simplicity, low-cost, and easy-operation features criteria. The results obtained through a numerical processing analysis validate the feasibility study of the proposed prototype.